2018
DOI: 10.1111/jtxs.12332
|View full text |Cite
|
Sign up to set email alerts
|

Rheological characterization of thickened protein‐based beverages under different food thickeners and setting times

Abstract: Food thickeners have been commonly used in the preparation of various thickened fluids with desirable rheological properties for dysphagic patients to elicit an optimal swallow response. However, among various thickened fluids, there is limited rheological information on cold thickened protein-based beverage (PBB) (e.g., whole milk, skim milk, and soybean milk) prepared with various xanthan gum (XG)-based thickeners. Our flow and dynamic rheological results showed that the flow and viscoelastic properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
4
12
0
1
Order By: Relevance
“…The NDD defines thickened liquids as thin (1–50 mPa·s), nectar-thick (51–350 mPa·s), honey-thick (351–1,750 mPa·s), and pudding-thick (> 1,750 mPa·s). Several researchers have studied the flow characterizations of various thickened liquids based on NDD thickness levels [567]. Recently, the International Dysphagia Diet Standardization Initiative (IDDSI) developed a standard framework for classifying thickened fluids by levels with a syringe flow test.…”
Section: Introductionmentioning
confidence: 99%
“…The NDD defines thickened liquids as thin (1–50 mPa·s), nectar-thick (51–350 mPa·s), honey-thick (351–1,750 mPa·s), and pudding-thick (> 1,750 mPa·s). Several researchers have studied the flow characterizations of various thickened liquids based on NDD thickness levels [567]. Recently, the International Dysphagia Diet Standardization Initiative (IDDSI) developed a standard framework for classifying thickened fluids by levels with a syringe flow test.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the higher concentration of FOS and psyllium husk in beverages compared to the other gums, these did not show a significant improvement in stabilizing the beverage samples. Xanthan gum at 3% (w/v) concentration was added to the whole milk, skim milk, and soybean milk showed 37.6 cP, 33.2 cP, and 41.7 cP viscosity, respectively (Kim & Yoo, ). Whereas Xu et al () showed better colloidal stability in juice samples due to better flexibility of gellan gum that resulted in more intermolecular associations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a study conducted previously by one of the author revealed n value of thickened fluids within the range of 0.16–0.39 (Hadde, Nicholson, & Cichero, 2015). A recent study on the rheology of protein‐based beverages using different food thickeners even observed a lower and narrower n value of only 0.14–0.21 (Kim & Yoo, 2018). Despite of these studies, there is still not enough literature evidences to specify a suitable range of shear thinning for thickened fluids.…”
Section: Thickened Fluidsmentioning
confidence: 99%